The Application of Diaphragm Ultrasound in Chronic Obstructive Pulmonary Disease: A Narrative Review - Heng Mu; Qunxia Zhang (COPD)
Chronic Obstructive Pulmonary Disease (COPD) is a prevalent condition that poses a significant burden on individuals and society due to its high morbidity and mortality rates. The diaphragm is the main respiratory muscle, its function has a direct impact on the quality of life and prognosis of COPD patients. This article aims to review the structural measurement and functional evaluation methods through the use of diaphragmatic ultrasound and relevant research on its application in clinical practice for COPD patients. Thus, it serves to provide valuable insights for clinical monitoring of diaphragm function in COPD patients, facilitating early clinical intervention and aiding in the recovery of diaphragm function.